2020
DOI: 10.3390/agronomy10101546
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a Bioregional Strategic Framework for a Sustainable Food System in Sicily

Abstract: The alignment of food systems with the Sustainable Development Goals (SDGs) is generally envisaged to make a positive impact on sustainability. This paper outlines some critical environmental and socio-economic indicators for Sicily in order to compare and explore the outcomes of two juxtaposing key drivers in a scenario planning exercise, where the extremities are Industrial versus Regenerative Agriculture/Agroecology and a Proactive versus Reactive government response. The most rational and less risky scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
9
0
2
Order By: Relevance
“…Thus, the authors concluded that now more than ever, multidisciplinary approaches involving agronomists, breeders, ecologists, food technologists, and economists will be critical for planning more sustainable and high-quality durum wheat production systems [ 232 , 233 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors concluded that now more than ever, multidisciplinary approaches involving agronomists, breeders, ecologists, food technologists, and economists will be critical for planning more sustainable and high-quality durum wheat production systems [ 232 , 233 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Vieira et al [13] define UFS as FS that encompasses activities and actors relating to cities' food supply and their interactions with the surrounding natural and built environments, socio-economic dynamics, and governance. With the growing recognition of the importance of FS in climate change and sustainable development around the world, other different types of FS have been introduced into academia and policymaking, such as sustainable food systems [14], [15], city region food system [16], [17], resilient food system [18], etc.…”
Section: Urban Food Systems (Ufs)mentioning
confidence: 99%
“…Examples include the Common Agricultural Policy (CAP) [365,366], The European Food and Nutrition Action Plan 2015-2020 [367], the Milan Urban Food Policy Pact [342], Nepalʹs Multisectoral Nutrition Plan (MSNP) 2013-2017 [349], Healthy food and beverage policy of the City of Hamilton (Ontario, Canada) [360], the Good Food Purchasing Policy (GFPP) in Los Angeles (USA) [368], the Local Food Strategy of Ghent (Belgium) [351]. Particular attention has also been paid to the linkages between sustainability transitions in agri-food systems and the achievement of the SDGs, especially SDG 2 "Zero Hunger" [35,36,[369][370][371][372][373][374]. Other articles have addressed synergies and/or trade-offs between policies and their instruments [312,375,376].…”
Section: Policy and Governancementioning
confidence: 99%
“…Bellver et al[431]; Basso and Antle[432]; Bazaluk et al[433];Becker et al [132]; Beingessner and Fletcher[434]; Bellows[287]; Ben Hassen et al[235]; Bencze et al[435]; Béné et al[386]; Béné et al[436]; Benítez et al[307]; Bentham et al[437]; Berti[438]; Bisht et al Borsellino et al[236]; Bounie et al[220]; Boyer and Ramaswami[209]; Boylan et al[441]; Brandão et al[442]; Braun et al[309]; Broekema et al[313]; Bryceson and Ross[443]; Bumbac et al[444]; Butler et al[213]; Cadel et al[445]; Cadillo-Benalcazar[365];Campbell [175]; Carino et al [446]; Carlsson et al [447]; Cazcarro et al [78]; Chable et al [196]; Chapman and Perkins [448]; Chen et al [76]; Chen et al [75]; Clay et al [449]; Coad and Pedley [450]; Colby [451]; Conner [452]; Covarrubias and Boas [106]; Cramer et al [308]; Culliford and Bradbury [453]; Dai et al [94]; Dalmoro et al[454]; Davies et al[455]; De Bernardi et al[411]; de Olde et al[456]; de Sousa and Solberg[457]; Derunova et al[458]; Derunova et al[459]; Di Vaio et al[460]; Diehl[214]; Dijkshoorn-Dekker et al[461]; Dillon et al[462]; Dorninger et al[463]; Giudice et al[98]; Granheim et al[485]; Guareschi et al[486]; Guarnaccia et al…”
mentioning
confidence: 99%